Disparities in the association between ambient temperature and preterm birth according to individual and regional characteristics: a nationwide time-stratified case-crossover study - Jieun Min; Whanhee Lee; Jongmin Oh; Youngrin Kwag; Eunji Kim; Joyce Mary Kim; Kyung A Lee; Eunhee Ha (BMC, 2024)
Abstract Background Several studies have reported that climate change elevates heat exposure in pregnant women and high temperatures during pregnancy are associated with preterm births (PTBs). Although the association might be disproportionate, related evidence remains sparse. We evaluated the disproportionate risk of PTB associated with ambient temperature during pregnancy by individual and regional characteristics in South Korea. Methods We collected data on birth certificates and daily mean temperatures during the period from 2011 to 2019. A time-stratified case-crossover design was used to investigate the association between temperature and PTB and stratified analyses were conducted to examine the effect modification of individual and regional characteristics. Results A total of 160,067 singleton PTBs were recorded in Korea from 2011 to 2019. A 5℃ increase in the mean temperature during the last four weeks before delivery was associated with an increased risk of PTB with an odds ratio (OR) of 1.03 (95% confidence interval [CI]: 1.02, 1.05), and the association was more evident in mothers aged ≥35 years (OR: 1.06 [95% CI: 1.03, 1.10]) and with low education levels (OR: 1.04 [95% CI: 1.02, 1.05]). Additionally, the estimated risk was evident in districts with lower medical resources and more prominent disparities were shown by individual and regional characteristics in rural areas than in urban areas. Conclusions This study provides evidence that the risk of PTB related to ambient temperature is disproportionate by individual and regional characteristics and suggests the need for public health policies to alleviate the disparities, especially in rural areas.